1981
DOI: 10.3109/00498258109045850
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the epoxy resin component 2,2-bis[4-(2,3-epoxypropoxy)phenyl]propane, the diglycidyl ether of bisphenol a (DGEBPA) in the mouse.; Part I. A comparison of the fate of a single dermal application and of a single oral dose of14C-DGEBPA

Abstract: 1. 14C-DGEBPA dermally applied to mice was only slowly eliminated in the feces (20% dose) and urine (3%), as a mixture of metabolites, over three days. Most of the applied radioactivity (66% dose) was extracted from the application area and its covering foil. 2. When 14C-DGEBPA was given orally to mice it was rapidly excreted; 80% of the administered 14C was eliminated in the feces and 11% in the urine 0-3 days after a single oral dose. 3. The urinary faecal metabolite profiles derived from dermal application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…A significant portion of the uncured decomposed material that is swallowed co be absorbed by the intestine. Climie et (19,20) studied the metabolic degradatic of 14C-BADGE in mice after the or administration of a single dose and found that 90% of the radioactivity was eliminated in feces and urine during the first 3 days of the experiment. Interestingly, a small k amount of BADGE (-5%) underwent F oxidative dealkylation to yield glycidaldehyde (which has alkylating properties) and V bisphenol-A, among other by-products (20).…”
mentioning
confidence: 99%
“…A significant portion of the uncured decomposed material that is swallowed co be absorbed by the intestine. Climie et (19,20) studied the metabolic degradatic of 14C-BADGE in mice after the or administration of a single dose and found that 90% of the radioactivity was eliminated in feces and urine during the first 3 days of the experiment. Interestingly, a small k amount of BADGE (-5%) underwent F oxidative dealkylation to yield glycidaldehyde (which has alkylating properties) and V bisphenol-A, among other by-products (20).…”
mentioning
confidence: 99%
“…A significant portion of the uncured or decomposed material that is swallowed can be absorbed by the intestine. Climie et al (19,20) studied the metabolic degradation of l4C-BADGE in mice after the oral administration of a single dose and found that 90% of the radioactivity was eliminat? ed in feces and urine during the first 3 days of the experiment.…”
mentioning
confidence: 99%
“…A separate experiment produced evidence that acetone facilitated the initial absorption of BADGE, undiluted BADGE being absorbed at a slower rate than the material dissolved in acetone. The urinary and faecal metabolite profiles from the dermal and oral studies were found to be similar and independent of the route of administration (8).…”
Section: Dermal Administrationmentioning
confidence: 87%
“…After 8 days 80.6% had been excreted in the faeces and 9.7% in the urine. The residual radioactivity (expressed as % of dose administered) in various tissues amounted to 0.11% in liver, 0.05% in kidneys, 0.03% in intestine, 0.16% in skin, 0.10% in blood, 0.05% in fat and 0.01% in the carcass (8).…”
Section: Oral Administrationmentioning
confidence: 99%